Combination of immunotherapy and other targeted therapies in advanced cutaneous melanoma - Riccardo Marconcini; Gaetano Pezzicoli; Luigia Stefania Stucci; Maria Chiara Sergi; Lucia Lospalluti; Camillo Porta; Marco Tucci (Taylor & Francis Group, 2022)
Cutaneous Melanoma (CM) is an aggressive cancer whose incidence is increasing worldwide. However, the knowledge of its biology and genes driving cell growth and survival allowed to develop new drugs that have improved PFS and OS of advanced disease. Both BRAF targeting agents and immune checkpoint inhibitors (ICIs) have been adopted for the treatment of metastatic disease and the adjuvant setting. Several melanoma patients show innate or acquired drug-resistance and thus new strategies are required for overcoming this complication. New ICIs have been developed, and strategies of combination or sequencing are under investigation in ongoing clinical trials. In addition, pre-clinical data have demonstrated that many strategies induce the release of neoantigens within the tumor microenvironment, thus suggesting the combination of new agents with ICIs. Here, we review the ongoing strategies in advanced CM including a dedicated section on treatment of brain metastases.